Estimates of clear-sky solar irradiances over Nigeria (2019)
This study attempts to circumvent the problem of paucity of input data required in climatology mapping of clear-sky solar irradiance in Nigeria by computing beam normal (Ebn) and diffuse (Ed) irradiances using a high performance broadband radiative model in the country climate zones. Air temperature, relative humidity and global datasets of ozone thickness and angstrom turbidity were used as input parameters. The biases in the Ebn estimates with NASA datasets across Nigeria (11e25%) are of similar magnitudes with NASA observations with ground measurements. The estimates show persistent negative biases that increased from tropical savannah to semi-arid climate zones (_8 to _24%). The bias in the Ed estimates is only of similar magnitude with NASA in semi-arid climate zone (10%). The Ed estimates show persistent negative biases that increase from semi-arid to tropical savannah across Nigeria (_7 to _54%). Also, the estimates in each climate zone correspond to the expected climatology of water vapour, aerosol turbidity and absolute optical mass. Lastly, the response of Ebn to water vapour absorption and aerosol extinction signals is mostly active in monsoon zone while the response to the signals by Ed are active in all the zones.